2007
DOI: 10.1080/09644010701211676
|View full text |Cite
|
Sign up to set email alerts
|

Changing public discourse on the environment: Danish media coverage of the Rio and Johannesburg UN summits

Abstract: Environmental degradation and unsustainable development were addressed on a global scale at the UN Summits in Rio de Janeiro in 1992 and Johannesburg in 2002. This chapter presents analyses of Danish television coverage of these two summits and related topics viewing the media stories as exemplary cases of wider public conceptions of the environment. Over a decade rhetoric about the summits and the environment changed, the agenda changed, and key environmental issues were repackaged. These changes are further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Framed by this notion, biodiversity discourses in EU documents shifted more and more towards conciliation and balance between ecological and economic goals, and further away from the intrinsic value of species. This arguably opened the way for a new notion to enter these documents: ''ecological modernization,'' which some authors believe is characteristic of present times (Baker 2007;Petersen 2007). Ecological modernization favors technology and economic entrepreneurs as the key actors for social change (Baker 2007;Petersen 2007) and defines nature as ''a 'standing reserve' of exploitable resources'' (Baker 2007, p. 303).…”
Section: Enacting and Resisting Social Changementioning
confidence: 97%
See 1 more Smart Citation
“…Framed by this notion, biodiversity discourses in EU documents shifted more and more towards conciliation and balance between ecological and economic goals, and further away from the intrinsic value of species. This arguably opened the way for a new notion to enter these documents: ''ecological modernization,'' which some authors believe is characteristic of present times (Baker 2007;Petersen 2007). Ecological modernization favors technology and economic entrepreneurs as the key actors for social change (Baker 2007;Petersen 2007) and defines nature as ''a 'standing reserve' of exploitable resources'' (Baker 2007, p. 303).…”
Section: Enacting and Resisting Social Changementioning
confidence: 97%
“…This arguably opened the way for a new notion to enter these documents: ''ecological modernization,'' which some authors believe is characteristic of present times (Baker 2007;Petersen 2007). Ecological modernization favors technology and economic entrepreneurs as the key actors for social change (Baker 2007;Petersen 2007) and defines nature as ''a 'standing reserve' of exploitable resources'' (Baker 2007, p. 303). As compared to the first ones, today's EU documents can also be said to accentuate the economic benefits of biodiversity protection by stressing now how ecosystems provide 'services' (see CEC 2006) in a vision compatible with a view of nature as a reserve of resources.…”
Section: Enacting and Resisting Social Changementioning
confidence: 97%
“…Gooch, 1995;Holbert et al, 2003;Riffe et al, 2007;Riffe & Hrach, 2009;Smith & Joffe, 2012;Sarrina Li, 2014). Climate change was not perceived as the most serious issue, even though it has dominated environmental news in recent years (Dispensa & Brulle, 2003;Antilla, 2005;Boykoff & Boykoff, 2007;Petersen, 2007;Gavin, 2009;Boykoff, 2009;Speck, 2010;Young & Dugas, 2011;Lyytim‰ki & Tapio, 2009;Lyytim‰ki, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Petersen (2007) found that ëalthough limits of growth was one prominent theme in 1992 in Danish television it was entirely absent in 2002, whilst coverage of criticism of the high cost and irrational priorities in environmental politics made an appearance.í Contrary to the discourse of ecological modernisation and sustainability, the issue of population growth was framed as an important environmental problem (Petersen, 2007).…”
Section: Media Coverage Of Environmental Issuesmentioning
confidence: 99%
“…1986; Stewart, Smith, and Denton 1989). One of the central analytic foci has been the development of a movement's discursive frame (Benford 2011; Petersen 2007; Snow 2004, 2008; Snow, Vliegenthart, and Cooigall‐Brown 2007). This socially constructed interpretation of history describes the origins of the movement, heroic exemplars of the movement, its process of development, and its future agenda (Benford 2002; Davis 2002).…”
Section: The Cultural and Institutional Dynamics Of Social Movementsmentioning
confidence: 99%